Change of structural condition of welded joints between high‐strength fine‐grained and structural steels - Hildebrand, Jörg; Werner, Frank (Journal of Civil Engineering and Management, 2004)
First, the production process of fine‐grained structural steels was considered. The results from the thermal calculation, which is a part of the welding simulation, were compared with measurements and good concordance was achieved. A modification of the hardness was found during the analysis of the hardness curve, the so‐called local hardness drop. The reason was the transformation of the structure, caused by thermal factors. The available TTA (time‐temperature‐austenite) and available TTT (time‐temperature‐transformation) diagrams do not describe this tempering process, which results in tempering structural condition by means of constituents of the martensite and bainite. The method of solution was applied to an example of a mismatch‐joint and a good concordance was achieved. First Published Online: 14 Oct 2010